Analysis of Hillslope Erosion Based on Excess Topography in Southeastern Tibet - Weiming Liu (Frontiers in Earth Science, 2021)
The southeastern Tibetan Plateau has been deeply dissected by major rivers and their tributaries into high-relief topography with deep gorges. In this region, most hillslope gradients in the high-relief areas approach a threshold value, and landslides are the dominant surface erosion process. For this work, we analyzed the hillslope erosion process by determining the excess topography from the threshold hillslope. Slope analysis found a similar normal distribution of slope values for six large drainage basins with different lithology, precipitation, and tectonic settings. Overall, 82% of the slopes in our study area were 30 ± 5°, so this was taken as a reasonable range of threshold hillslope angles. We determined that the excess topography calculated for different threshold values all occur along major fluvial inner gorges. We found a linear relationship between excess topography and the mean erosion rate in drainage basins, which indicates that hillslope erosion, especially landslides, is the main erosion process. In contrast, the correlation between excess topography and the slope is only found for low-relief topography. This suggests that excess topography is a better metric than the slope to reflect the spatial distribution of erosion rates in the southeastern Tibetan Plateau. In addition, for a threshold value of 30°, we collected data from 4,430 landslides and found that 71% of these landslides had occurred in an area of excess topography. This implies that most recent landslides did not reduce the slope below the threshold value. As a result, the potential for future landslides remains high in areas where landslides have recently occurred.